Temporal variation, habitat heterogeneity and anthropogenic stressors influencing wildlife communities in an oxbow shaped wetland of lower Ganges floodplain, Bangladesh - Jaman, M F; Alam, M M; Rabbe, M F; Shome, A R (Journal of Biodiversity Conservation and Bioresource Management, 2023)
Marjat baor is an Ecologically Critical Area located at the lower Ganges floodplain of Bangladesh. A yearlong study wildlife status, community structure and seasonal effect was made following direct field observation in the Marjat baor. A total of 186 vertebrate wildlife species (14 amphibians, 21 reptiles, 131 birds and 19 mammals) were recorded with 9402 individuals. Wetland habitat specialist species were abundant in the community where, Dendrocygna javanica was at the top (5.85%). Herpetofauna showed more uneven distribution than the other animal groups. Due to the richness of migratory birds, seasonal variation showed the highest number of unique species in winter season. A significant difference observed between the community structure of human-dominant and non-dominant landscapes in the ANOSIM test (R = 0.146, p <0.021) and NMDs plot. Floating plant and homestead forest around the baor held the maximum wildlife species. Species richness (F=11.334, p=0.0009) and abundance (F=68, p= 0.0021) differed significantly among the five microhabitats of the study area. The presence of eight threatened wildlife species was noticed in the study area. Anthropogenic stressors causes existential crisis for wildlife. It is revealed that, the community-based conservation may be helpful for conserving the wildlife species in the study area. This study may play a significant role in taking future conservation initiatives. Biodivers. Conserv. Bioresour. Manag. 2023, 9(2): 83-98